Computational-experimental integration identifies potent carbohydrate-hydrolyzing enzyme inhibitors from Nardostachys jatamansi: molecular docking, dynamics and pharmacokinetic predictions - Iqbal, Muhammad Javid; Malik, Iqra; Bernal, Gonzalo; Salas-Burgos, Alexis M.; Salazar, Luis A. (Frontiers in Pharmacology, 2026)
BackgroundCurrent α-glucosidase and α-amylase inhibitors demonstrate limited therapeutic efficacy and significant gastrointestinal side effects, necessitating identification of novel antidiabetic agents. This study employed integrated computational and experimental approaches to evaluate carbohydrate hydrolyzing enzyme inhibitory potential of Nardostachys jatamansi and its phytochemicals.Material and methodsPlant extracts were evaluated through enzymatic assays against α-glucosidase and α-amylase. Virtual screening of 144 phytochemicals employed molecular docking, followed by molecular dynamics simulations (100 ns) and density functional theory calculations at B3LYP/6-311++G(d,p) level. ADMET profiling assessed drug-likeness potential.ResultsN. jatamansi extract demonstrated superior enzyme inhibition compared to acarbose: IC50 values of α-glucosidase 61.7 ± 3.9 μg/mL and α-amylase 81.3 ± 4.7 μg/mL versus 132.6 ± 7.8 μg/mL and 112.1 ± 6.2 μg/mL respectively. Molecular docking identified Virolin with selective α-glucosidase affinity (−9.6 kcal/mol) and Nardostachysin showing high α-amylase binding (−9.5 kcal/mol). Molecular dynamics revealed Nardostachysin-α-amylase complex stability (ΔG = −158.51 kcal/mol) throughout simulation, while Virolin-α-glucosidase complex showed late-stage dissociation. DFT calculations revealed HOMO-LUMO gaps of 4.78 eV (Virolin) and 4.57 eV (Nardostachysin) with distinct dipole moments of 4.83 and 6.29 Debye respectively. ADMET analysis confirmed favorable drug-likeness with complete Lipinski compliance and zero PAINS alerts for both lead compounds.ConclusionN. jatamansi extract demonstrated experimentally superior enzyme inhibition compared to acarbose, while computational analysis identified Virolin and Nardostachysin as promising drug candidates, establishing a validated integrative approach for accelerating natural product antidiabetic lead discovery.